Human platelet antigens in Burmese, Karen and north‐eastern Thais. Issue 1 (3rd October 2016) - Phuangtham, R.; Romphruk, A.; Puapairoj, C.; Leelayuwat, C.; Romphruk, A. V.
SUMMARY: Objectives: A comparative study of allele frequencies at HPA‐1 to ‐6 and HPA‐15 in Burmese and Karen populations as well as at HPA‐15 in north‐eastern Thais (NET) is presented. Background: Human platelet antigens (HPAs) are clinically important in several immune platelet disorders, including foetal and neonatal alloimmune thrombocytopenia (FNAIT), post‐transfusion purpura (PTP) and platelet transfusion refractoriness (PTR). The knowledge of antigen frequencies in a population is essential for the evaluation of patients suffering from immune‐mediated platelet disorders. Methods: A total of 285 unrelated, healthy Burmese, 242 Karen and 300 NET were recruited to this study. Genotype and allele frequencies of HPA‐1 to ‐6 and HPA‐15 were defined using polymerase chain reaction sequence‐specific primers (PCR‐SSP) Results: No individuals homozygous for HPA‐1bb, ‐2bb, ‐4bb, ‐5bb and ‐6bb were detected. HPA‐1a, ‐2a, ‐4a, ‐5a and ‐6a were present in all samples of Burmese and Karen origin. HPA‐1b, ‐2b, ‐4b, ‐5b and ‐6b were rare in these populations. The frequencies of HPA‐3a/‐3b were 60·4/39·6% in Burmese and 55·8/44·2% in Karen, respectively. Frequencies of HPA‐15a/‐15b were 57·2/42·8% in Burmese, 52·5/47·5% in Karen and 49·8/50·2% in NET. Conclusions: The frequencies of HPA genotypes in our study indicates that HPA‐1a, ‐2a, ‐4a, ‐5a and ‐6a are unlikely involved in FNAIT, PTP and PTR in Burmese and Karen populations. However, HPA‐1b, ‐2b, ‐3a, ‐3b, ‐4b, ‐5b, ‐6b, ‐15a and ‐15b may likely stimulate alloantibodies in these populations.